STRESS, PERSONALITY AND MIGRAINE. A REVIEW OF PSYCHOSOCIAL AND NEUROPHYSIOLOGICAL RISK FACTORS - Sofiya Salash,; Aleksandra Romaniuk,; Artur Koza,; Anna Karcz,; Barbara Pająk,; Hubert Bołdys-Żegocki,; Jakub Majewski,; Maria Kaniecka,; Małgorzata Dworniczak,; Oliwia Wróblewska, (International Journal of Innovative Technologies in Social Science, 2025)
Migraine is a complex neurological and psychological condition that causes repeated headache attacks, sensitivity to light and sound, and major effects on quality of life. Modern research shows that migraine develops from the interaction between biological sensitivity, stress, and personality traits. This review combines findings from neuroscience, psychology, and clinical studies to explain how stress reactivity, emotional regulation, and coping style affect migraine onset and management. Understanding these biological and psychosocial links can improve treatment and support more effective combined approaches that use both medication and psychotherapy.